Sensitivity and specificity of mean platelet volume as a laboratory marker for irritable bowel syndrome: Can it be added to Rome criteria? - Mostafa Vaghari-Tabari; Soheila Moein; Durdi Qujeq; Mehrdad Kashifard; Haydeh Alaoddolehei; Karimollah Hajian-Tilaki (AOSIS, 2020)
Background: Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder. Objective: This study aimed to evaluate red blood cell distribution width (RDW) and mean platelet volume (MPV) as laboratory markers to discriminate IBS patients from both healthy controls and patients with inflammatory bowel disease (IBD). Methods: This case-control study enrolled patients referred to Ayatollah Rouhani Hospital, Endoscopy Department, Babol, Iran, for colonoscopy examination from 2015 to 2017. Fifty IBS patients were selected from among patients who had undergone a normal colonoscopy and showed symptoms matching the Rome III criteria. Fifty healthy participants and 50 IBD patients, matched for sex and age, were also enrolled in this study. Both RDW and MPV were measured and analysed by independent sample t-test and receiver operating characteristic curve analysis. A p-value of less than 0.05 was considered statistically significant. Results: While RDW was higher and MPV was lower among IBS patients compared to healthy controls (p = 0.047 and p = 0.001), there were no significant differences in RDW or MPV levels between IBS and IBD patients. The area under the curve of RDW in the discrimination between IBS and IBD was 0.620 (p = 0.039), and the area under the curve of MPV in the discrimination between healthy controls and IBS patients was 0.801 (p = 0.001). Conclusion: Mean platelet volume is potentially a useful laboratory marker for distinguishing between IBS patients and healthy individuals. Red blood cell distribution width should be considered as a potential marker to distinguish among IBS and IBD patients.